An alliance to secure electoral victory - Jawan, Jayum (Australian National University, 2016)
Conflict has raged within and among Malaysia’s political parties this year over controversial legislation regarding Islamic law, but Jayum Anak Jawan argues it is all part of the Prime Minister’s political strategy to win the next election